Ruptured Bilateral Pericallosal Artery Aneurysm in Mirror Position: Case Report - Meguins, Lucas Crociati; Valsechi, Linoel Curado; Fernandes, Ronaldo Brasileiro de Miranda Batista; Morais, Dionei Freitas; Spotti, Antonio Ronaldo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction Pericallosal artery (PA) aneurysms represent 2 to 9% of all intracranial aneurysms, and their management remains difficult.Objective The aim of the present study is to describe the case of an adult woman with subarachnoid hemorrhage and bilateral PA aneurysm in mirror position.Case Report A 46-year-old woman was referred to our institution 20 days after a sudden severe headache. She informed that she was treating her arterial hypertension irregularly, and consumed ∼ 20 cigarettes/day. The patient was neurologically intact at admission. A non-contrast computed tomography (CT) on the first day of the onset of the symptoms revealed hydrocephaly and subarachnoid hemorrhage (Fisher III). An angio-CT/digital subtraction arteriography showed bilateral PA aneurysms in mirror position. The patient was successfully treated with surgery via the right interhemispheric approach (because the surgeon is right-handed); the surgeon performed the proximal control with temporary clipping, and introduced an external ventricular drain at the end of the surgery. The patient was discharged on the fourth postoperative day without any additional neurological deficits or ventricular shunts.Conclusion Ruptured PA aneurysm is a surgically challenging aneurysm due to the many anatomical nuances and risk of rebleeding. However, the operative management of ruptured bilateral PA aneurysms is feasible and effective.
Keywords: pericallosal artery aneurysms